Movements in Parties: OccupyPD - Donatella della Porta (Coordinamento SIBA, 2015)
When the United States activists called for people to Occupy#everywhere, it is unlikely they were thinking of the headquarters of the Italian centre-left party. Parties and movements are often considered to be worlds apart. In reality, parties have been relevant players in movement politics, and movements have influenced parties, often through the double militancy of many of their members. OccupyPD testifies to a continuous fluidity at the movement-party border, but also to a blockage in the party’s interactions with society that started long before the economic crisis but drastically accelerated with it. In this paper we present the OccupyPD Movement as a case of interaction between party politics and social movement politics, and in particular between the base membership of a centre-left party and the broader anti-austerity movement that diffused from the US to Europe adopting similar forms of actions and claims. Second, by locating it within the context of the economic and democratic crisis that erupted in 2007, we understand its emergence as a reaction towards politics in times of crisis of responsibility, by which we mean a drastic drop in the capacity of the government to respond to citizens’ requests. To fulfil this double aim, we bridge social movement studies with research on party change, institutional trust and democratic theory, looking at some political effects of the economic crisis in terms of a specific form of legitimacy crisis, as well as citizens’ responses to it, with a particular focus on the political meaning of recent anti-austerity protests. In this analysis, we refer to both quantitative and qualitative data from secondary liter-ature and original in-depth interviews carried out with a sample of OccupyPD activists.